Transitive Sentence in The Short Story Haflah Tharb by Muhammad Taymour: A Tagmemic Perspective of Kenneth L. Pike - Nurul Khadroh; Penny Respati Yurisa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the forms and functions of verbal sentences in the short story Haflah Tharb by Muhammad Taymour based on Kenneth L. Pike’s Tagmemic theory. The research employs a descriptive qualitative approach. The data consist of sentences and phrases found in the short story Haflah Tharb by Muhammad Taymour. The data were collected using reading, translating, and note-taking techniques. Data analysis was conducted using the Miles and Huberman model, which includes three stages: data reduction, data display, and conclusion drawing. The results reveal four patterns of transitive sentence structures in Haflah Tharb: (1) P + S + O; (2) P + S + O + Adj; (3) P + O + S; and (4) P + S + Adj + O. Each pattern is analyzed in terms of slots, classes, roles, and cohesion, all of which require the presence of an object to complete the meaning of the transitive predicate. This study contributes theoretically by applying Pike’s tagmemic analysis to modern Arabic literary texts. Specifically, it identifies variations in transitive syntactic patterns that enrich the understanding of Arabic sentence structure in a narrative context.